Impact of COVID-19 Vaccine on Hearing Status of Young Ages (Medical College Students as a Sample) - Mazin Kamil Hamid (مجلة بغداد للعلوم)
Many studies dealt with the consequences of  SARS CoV-2  (which cause COVID-19 infection) on the nervous system especially sensory nerves where the virus causes loss of taste and smell as it’s known, and may affect auditory nerves and be the expected cause of some hearing problems. A case-control analytic study was performed on a connivance sample of society of university students from a medical faculty. Each participant filled out a questionnaire contains demographic data and general, auditory and respiratory health condition, in addition to vaccination status. In the other side, the audio- examinations were performed on the study sample including Pure Tone Audiometry (PTA) and tympanometry. Two statistical methods; chi-square and t-test were used to interpret the correlation.  It is noticeable that there is no clear link between the thresholds and the vaccination status. This is contrary to some studies that found that the vaccine may have a very slight influence on hearing thresholds. This can be explained by the fact that is the small (significant) p values ​​in both methods was spread in a various and random manner, and it can be said that there is a possible effect, but it is not clear nor regular. A more comprehensive studies are required to establish this relationship between the hearing threshold and the COVID-19 vaccine.